Pengembangan Media “Wayang Si Dupan” untuk Pembelajaran Siklus Hidup Hewan di Sekolah Dasar - Desy Herawati (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
Each student has a different character. Therefore, teachers are required to be able to create learning that can meet students' diverse learning needs. When studying Animal Life Cycles, the teacher used video learning media, but at that time only children with visual and auditory learning styles were able to follow the lesson well, while children with kinesthetic learning styles felt bored and ended up making noise and disturbing other friends. Based on this problem, the teacher finally developed his learning media by creating Wayang Si Dupan media. This development research aims to test the validity and effectiveness of the Wayang Si Dupan media in learning animal life cycles in class 4 at SDN Mangunharjo 7, Probolinggo City. This research uses a 4D model, namely define, design, development, and dissemination. Material expert validation results for Wayang Si Dupan media obtained an average of 87% and validation results from design experts obtained an average of 91%. Students' learning outcomes in the Animal Life Cycle material increased by 78% after they used the Wayang Si Dupan media. This shows that Si Dupan Wayang Media is effective in improving student learning outcomes.